The long-term outcome of simple trapeziectomy. (February 2019) - Yeoman, Thomas F. M.; Stone, Oliver; Jenkins, Paul J.; McEachan, Jane E.
The aim of this study was to investigate the long-term outcome of simple trapeziectomy by a single surgeon and to compare this with pre-operative function. Two hundred and five patients completed the shortened disabilities of the arm, shoulder and hand questionnaire (QuickDASH) and the EuroQoL five-dimensional questionnaire (EQ-5D) scores at a mean of 8.2 (range 3.5–17) years after simple trapeziectomy. There were no pre-operative scores available, so case controls were selected from our prospective database to compare pre- and post-operative patient-reported outcome measures. The mean QuickDASH score of the post-operative matched group was 37 (SD 17.0) and the mean EQ-5D was 0.56 (SD 0.31). The mean QuickDASH score of the pre-operative group was 54 (SD 17.0). The mean difference in QuickDASH between the pre- and post-operative groups was 17 (95% CI: 8 to 26, p = 0.0003). This study demonstrated a significant and sustained improvement in patient-reported function after simple trapeziectomy. It supports that simple trapeziectomy is a simple, safe and effective treatment for advanced trapeziometacarpal joint arthritis. Level of evidence: IV